Une union économique et monétaire entre Haïti et la République dominicaine est-elle aujourd’hui une option concevable ? - Louis Dupont (Études Caribéennes)
This paper uses an unobserved component model to analyse the feasibility of economic and monetary union (EMU) between Haiti and Dominican Republic, two countries sharing the same island but whose history is one conflict and divergent economic prospects. In spite of these historical obstacles, is it possible to plan an economic and monetary union among these economies? The objective of this paper is to provide a framework to identify and evaluate the asymmetry degree of macroeconomic shocks within these economies in order to appreciate the viability of this project, also the nature of these potential benefits and costs. The results show the fragility of this process because of the weak economic policy convergence among these countries. The shocks disintegration stemming from our model confirm these results and suggests that at this stage, several economic criteria are not satisfied for the two countries to fully benefit from an economic and monetary union. However, the endogeneity of most of these criteria militates in favour of an agenda for progressive integration between them.